Ginsenoside Rb1 Enhances Atherosclerotic Plaque Stability by Improving Autophagy and Lipid Metabolism in Macrophage Foam Cells - Qiao, Lei; Zhang, Xue; Liu, Minghao; Liu, Xiaoling; Dong, Mei; Cheng, Jing; Zhang, Xinyu; Zhai, Chungang; Song, Yu; Lu, Huixia; Chen, Wenqiang (Frontiers in Pharmacology, 2017)
Atherosclerosis is a lipid-driven disease in which macrophage foam cells play a critical role by increasing vascular lipid accumulation and contributing to plaque instability. Ginsenoside Rb1 (Rb1), the most abundant active component of ginseng, was found potentially to promote lipid metabolism and attenuate lipid accumulation. However, the underlying mechanisms remain unclear. In this study, the effects of Rb1 on lipid accumulation and plaque stability were investigated both in vitro and in vivo by using primary peritoneal macrophages isolated from C57BL/6 mice and atherosclerosis model in ApoE-/- mice. The results showed that Rb1 reduced lipid accumulation both in macrophage foam cells and atherosclerotic plaque. Our results demonstrated that Rb1 treatment promoted plaque stability by modifying plaque composition via the activation of autophagy both in vitro and in vivo. Transmission electron microscope further showed an increased accumulation of autophagolysosomes in Rb1-treated macrophage foam cells. However, the modulation of Rb1 on lipid accumulation was attenuated by blockage of autophagy using autophagy-related gene5 (Atg5) small interfering RNA (siRNA) in vitro. In addition, Rb1 notably increased AMPK phosphorylation both in vitro and in vivo, which was abolished by AMPK inhibitor compound C in Rb1-induced autophagy in macrophage foam cells. In conclusion, Ginsenoside Rb1 reduced lipid accumulation in foam cells and enhanced atherosclerotic plaque stability by the induction of macrophage autophagy. Our study provides new evidence for possibility of Rb1 in prevention and treatment of atherosclerosis.